Multimodal Breast Image Registration: Mapping MRI and Surface Data - Pedro Henrique Moreira Queirós Carvalho (2018)
This project has the objective of matching breast MRI data to surface information. This allows the creation of complete 3D models of the breast, which might have clinical implementation. The difficulties lie in the difference of pose during acquisition of the data, leading to a completely different breast shape in MRI and Surface information. First, coarse registration is applied to roughly align both inputs, involving rotation, translation and a rigid Iterative Closest Points algorithm. The fine registration is done using the Free Form Deformation technique. This approach has shown promising results.